Severe interstitial lung disease risk prediction in anti-melanoma differentiation-associated protein 5 positive dermatomyositis: the STRAD-Ro52 model - Fei Xiao; Feilong Chen; DongSheng Li; Songyuan Zheng; Xiao Liang; Juan Wu; JunYuan Zhong; Xiangliang Tan; Rui Chen; Junqing Zhu; Shixian Chen; Juan Li (Annals of Medicine)
Objective Anti-melanoma differentiation-associated gene 5-positive dermatomyositis-associated interstitial lung disease (MDA5+DM-ILD) often leads to acute respiratory failure and endangers lives. This study quantitatively analysed chest high-resolution computed tomography (HRCT) images to assess MDA5+DM-ILD and establish a risk prediction model for severe ILD within six months.Methods We developed a ‘Standardized Threshold Ratio Analysis & Distribution’ (STRAD) to analyse lung HRCT images. In this retrospective study, 51 patients with MDA5+DM-ILD were included and divided into severe-ILD and non-severe-ILD groups based on the occurrence of acute respiratory failure within six months post-diagnosis of MDA5+DM. The STRAD parameters, clinical indicators and treatments were compared between the two groups. Least absolute shrinkage and selection operator (LASSO) regression was used to select the optimal STRAD parameters. Multivariate analysis selected clinical factors to be further combined with STRAD to enhance the predictive performance of the final model (STRAD-Ro52 model).Results Significant differences were observed between the two groups in STRAD parameters, anti-Ro52 antibody titers, presence of anti-Ro52 antibodies, age, ESR, ALB, Pa/FiO2, IgM and IL-4 levels. The STRAD parameters were significantly correlated with demographic, inflammatory, organ function and immunological indicators. Lasso logistic regression analysis identified the −699 to −650 HU lung tissue proportion (%V7) as the optimal parameter for predicting severe ILD and S6·%V7, and the distribution of %V7 in the mid lungs was the optimal space parameter. Multifactorial regression of clinical indicators showed that the presence of anti-Ro52 antibodies was an independent risk factor for severe ILD, leading to the establishment of the STRAD-Ro52 model.Conclusions The STRAD-Ro52 model assists in identifying MDA5+DM patients at risk of developing severe ILD within six months, further optimizing precise disease management and clinical research design.